Evaluation of three portable blood lactate analysers: Lactate Pro, Lactate Scout and Lactate Plus - Tanner, R. K.; Fuller, K. L.; Ross, M. L. R. (European Journal of Applied Physiology, 2010)
Three portable blood lactate analysers, Lactate Pro (LP), Lactate Scout (LS) and Lactate Plus (L+), were evaluated. Analyser reliability and accuracy was assessed. For reliability, intra- and inter-analyser comparisons demonstrated that the LP (intra-TE = 0.5 mM, inter-TE = 0.4 mM) and L+ (intra-TE = 0.4, inter-TE = 0.4 mM) displayed greater overall reliability than the LS (intra-TE = 1.0, inter-TE = 0.8 mM). At BLa < 4.0 mM, the LP (intra-TE = 0.1 mM) demonstrated greater reliability than the LS (intra-TE = 0.5 mM) and L+ (intra-TE = 0.4 mM). At BLa > 8.0 mM, the LP (intra-TE = 0.5 mM, inter-TE = 0.4 mM) and L+ (intra- and inter-TE = 0.4 mM) displayed greater reliability than the LS (intra-TE = 1.1 mM, inter-TE = 0.9 mM). For accuracy, the L+ (SEE = 0.6 mM) compared more favourably to the LP than the LS (SEE = 1.1 mM). At BLa ~1.0-18.0 mM, the LS produced values that were up to 0.9 mM higher than the LP; the L+ produced BLa that were within ±0.1 mM. All portable analysers tended to under-read the ABL 700 analyser. The suitability of the LP and L+ as accurate analysers is supported by strong correlations (r = 0.91 and r = 0.94) and limits of agreement =2.1 mM. This study showed that the LP and L+, compared well to each other, displayed good reliability and accuracy when compared to a laboratory-based analyser. Although the LS also displayed relatively good reliability, it was not as reliable or accurate as the LP or L+.